"GLACAROL": Penciptaan Ekonomi Sirkular melalui Pemanfaatan Limbah Batok Kelapa Menjadi Briket, Pensil, dan Artistik Powder - Dhiah Agustina Qahar; Agus setiawan; Feri Setiawan; Salahuddin Abdul Aziz (Jurnal Pengabdian kepada Masyarakat, 2025)
This community engagement project investigated the valorization of coconut shell waste in Glagah Village, Indonesia, through the development of "GLACAROL," a line of value-added charcoal-based products: briquettes, drawing pencils, and art powders. Employing a participatory design, the initiative included community surveys, production training, and product branding. Results indicated significant reductions in waste volume, lessened environmental impacts (soil and water), and heightened community environmental awareness. The “GLACAROL” brand demonstrated potential for income enhancement via new employment and product sales, although scalability and process optimization challenges persist. The project presents a promising model for community-based waste management and sustainable development and emphasizes the potential of turning local waste into marketable goods. Long-term monitoring and continued support are essential for replication and durability of the outcomes.